Roy and Zhores Medvedev Loyal Dissent in the Soviet Union Barbara Martin - Martin, Barbara (Academic Studies Press, 2024)
The unique trajectory of Soviet dissident twin brothers Roy and Zhores Medvedev takes us through a century of history, from Stalin to Putin. They achieved fame as the first authors of independent research on Stalinism from within the USSR, but their lives were also marked by controversy.